A Complete Examination of Bacillus thuringiensis: Its Properties and Functions of Proteins - KP, Hasna; EV, Rasheeda (Journal of Neonatal Surgery, 2025)
Bacillus thuringiensis is an ubiquitous, gram-positive, aerobic, endospore-forming environment-friendly bacterium. The development of this bacterium brings the most significant advances in crop protection technology. Bacillus thuringiensis produces various types of insecticidal proteins, including Cry, Cyt, Vip (vegetative insecticidal proteins), and Sip (secreted insecticidal proteins), each with distinct modes of action and target specificities. Cry protein is famous in its insecticidal activity against many insect species . Cyt proteins exhibit broad cytotoxic activity against both invertebrate and vertebrate cells (Bravo et al., 2007). Besides this protein Bacillus thuringiensis also produces Vip (vegetative insecticidal proteins) and Sip (secreted insecticidal protein), both of which have insecticidal activity. Vip proteins are divided into four groups Vip1, Vip2, Vip3, and Vip4 (Palma et al., 2014). The organism also exhibits parasporal crystals during the stationary phase of its growth cycle, making it a unique organism from others (Moazamian et al., 2018). These proteinaceous bodies reported several distinctive characteristics, and crystals have unique toxic activities against certain insects and some other invertebrates (Charles et al. 2000) and human cancer cells (Mizuki et al., 2000)